Mapping Sustainable Marketing Using Bibliometric Analysis - F Fitria; Desi Tia Adisti; D Dea; Agum Gumelar; Adi Setiawan (CV. Media Digital Publikasi Indonesia, 2024)
Research on sustainable marketing is mapped using bibliometric analysis, which offers a thorough picture of the field's current condition and future directions. By means of bibliometric analysis using VosViewer and the collection of 1.385 articles, the study indicates a noteworthy increase in publications and citations concerning the subject matter during the last ten years. Several important clusters actively studying Sustainable Marketing, including sustainable consumer behavior, sustainability orientation, consumption patterns, market segmentation, and stakeholder roles, were found through analysis of author collaboration patterns.